Developing and pilot testing a comprehensive health literacy communication training for health professionals in three European countries. Issue 1 (January 2018) - Kaper, Marise S.; Sixsmith, Jane; Koot, Jaap A.R.; Meijering, Louise B.; van Twillert, Sacha; Giammarchi, Cinzia; Bevilacqua, Roberta; Barry, Margaret M.; Doyle, Priscilla; Reijneveld, Sijmen A.; de Winter, Andrea F.
Highlights: We identified evidence-based Health Literacy Communication training components. We developed a patient-centred training to address various health literacy problems. The training developed fits the needs of health professionals from multiple disciplines. Professionals reported perceived improvement in health literacy communication. Abstract: Objective: Skills to address different health literacy problems are lacking among health professionals. We sought to develop and pilot test a comprehensive health literacy communication training for various health professionals in Ireland, Italy and the Netherlands. Methods: Thirty health professionals participated in the study. A literature review focused on evidence-informed training-components. Focus group discussions (FGDs) explored perspectives from seventeen professionals on a prototype-program, and feedback from thirteen professionals following pilot-training. Pre-post questionnaires assessed self-rated health literacy communication skills. Results: The literature review yielded five training-components to address functional, interactive and critical health literacy: health literacy education, gathering and providing information, shared decision-making, enabling self-management, and supporting behaviour change. In FGDs, professionals endorsed the prototype-program and reported that the pilot-training increased knowledge and patient-centred communication skills in addressing health literacy, as shown by self-rated pre-post questionnaires. Conclusion: A comprehensive training for health professionals in three European countries enhances perceived skills to address functional, interactive and critical health literacy. Practice implications: This training has potential for wider application in education and practice in Europe.